Medicinal chemistry perspectives of 1, 2, 3, 4-tetrahydroisoquinoline analogs – biological activities and SAR studies. Issue 20 (29th March 2021) - Faheem,; Karan Kumar, Banoth; Chandra Sekhar, Kondapalli Venkata Gowri; Chander, Subhash; Kunjiappan, Selvaraj; Murugesan, Sankaranarayanan
Abstract : This review provides critical insights into the biological activities and Structure–Activity Relationship (SAR) studies of tetrahydroisoquinoline (THIQ) analogs. Abstract : Isoquinoline alkaloids are a large group of natural products in which 1, 2, 3, 4-tetrahydroisoquinolines (THIQ) form an important class. THIQ based natural and synthetic compounds exert diverse biological activities against various infective pathogens and neurodegenerative disorders. Due to these reasons, the THIQ heterocyclic scaffold has garnered a lot of attention in the scientific community which has resulted in the development of novel THIQ analogs with potent biological activity. The present review provides a much-needed update on the biological potential of THIQ analogs, their structural–activity relationship (SAR), and their mechanism of action. In addition, a note on commonly used synthetic strategies for constructing the core scaffold has also been discussed.